2022
DOI: 10.18632/aging.204284
|View full text |Cite
|
Sign up to set email alerts
|

Age-related metabolic and neurodegenerative changes in SAMP8 mice

Abstract: The most important risk factor for the development of sporadic Alzheimer's disease (AD) is ageing. Senescence accelerated mouse prone 8 (SAMP8) is a model of sporadic AD, with senescence accelerated resistant mouse (SAMR1) as a control. In this study, we aimed to determine the onset of senescence-induced neurodegeneration and the related potential therapeutic window using behavioral experiments, immunohistochemistry and western blotting in SAMP8 and SAMR1 mice at 3, 6 and 9 months of age. The Y-maze revealed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 83 publications
1
4
0
Order By: Relevance
“…Male mice were used for all the experiments. Their body weights at the beginning of the experiments were (average ± SEM): R1 nonTg 31.03 ± 0.75 g, R1 α-SynTg 29.78 ± 0.54 g, P8 nonTg 26.56 ± 0.62 g and P8 α-SynTg 26.90 ± 1.68 g. Experimental groups in SAMP8 strain weighted less than SAMR1 groups at all ages, as it has been previously described 32 .
Figure 1 Experimental design and model validation.
…”
Section: Methodssupporting
confidence: 60%
“…Male mice were used for all the experiments. Their body weights at the beginning of the experiments were (average ± SEM): R1 nonTg 31.03 ± 0.75 g, R1 α-SynTg 29.78 ± 0.54 g, P8 nonTg 26.56 ± 0.62 g and P8 α-SynTg 26.90 ± 1.68 g. Experimental groups in SAMP8 strain weighted less than SAMR1 groups at all ages, as it has been previously described 32 .
Figure 1 Experimental design and model validation.
…”
Section: Methodssupporting
confidence: 60%
“…SAMP8 mice are characterized by an early onset of age-related disorders accompanied by neuronal injury as early as 6 months old ( Pacesova et al, 2022 ). Among all SAMP mouse strains, SAMP8 mice show senescence deterioration in cognitive function compared with senescence-resistant (SAMR1) control mice ( del Valle et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among all SAMP mouse strains, SAMP8 mice show senescence deterioration in cognitive function compared with senescence-resistant (SAMR1) control mice ( del Valle et al, 2012 ). SAMP8 is a widely used mouse model of aging and dementia ( Takahashi, 2010 ; Pacesova et al, 2022 ). Meanwhile, other AD animal models such as APP/PS1 transgenic mouse, 3XTg AD mouse, and 5XFAD mouse are transgenic mice that mimic histological damages in the brain involved in Aβ or Tau, not reflecting aging-related changes.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, it was found that cholinergic system dysfunction improvement of KXS was significantly correlated with regulation of the nicotinic acetylcholine receptor CHRNB2. Senescence accelerated mouse prone 8 (SAMP8) was reported to develop typical AD pathologies, such as an abnormal expression of anti-aging factors, inflammation, oxidative stress, tau hyperphosphorylation, amyloid-(A) deposits, abnormal autophagy activity, and endoplasmic reticulum stress ( Andrea et al, 2022 ). Therefore, SAMP8 is widely used and considered as an ideal model for AD research, displaying age-related cognitive decline and memory loss ( Xie et al, 2020 ).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%